Eva Mroczek, The Literary Imagination in Jewish Antiquity. (2nd May 2019) - Beebe, Jacob
Abstract : Eva Mroczek, The Literary Imagination in Jewish Antiquity. New York: Oxford University Press, 2016, pp. ix + 190, ISBN: 9-780-19088-608-0 (pbk).